2016
DOI: 10.1002/biof.1295
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity efficacy of GLP‐1 receptor agonist liraglutide is associated with peripheral tissue‐specific modulation of lipid metabolic regulators

Abstract: To investigate the role of glucagon-like-peptide-1 receptor (GLP-1R) in peripheral lipid metabolism. Both lean and high-fat diet (HFD)-induced obesity (DIO) rats were used to compare the peripheral effects of the subcutaneous and repeated administration of the GLP-1R agonist liraglutide on the expression of key regulators involved in lipid metabolism, β-oxidation and thermogenesis in liver, abdominal muscle, and epididymal white adipose tissue (eWAT). We observed that liraglutide reduced caloric intake, body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 48 publications
5
30
0
1
Order By: Relevance
“…In our current study, the mice were subjected to the CLAMS system for analysis of metabolic status at the end of the experiment, but the weight reduction effect was seen after the first drug injection and maintained throughout the experiment, rendering the possibility that we might have missed the best time window to quantify EE that significantly influences body weight gain. Nevertheless, our data that Supaglultide-treated mice demonstrated a concomitantly increased trend of EE both on per-whole-animal and BW-normalized basis suggested that supaglutide exerted a regulatory effect on the energy expenditure of the obese mice, which is in good agreement with previous studies in both preclinical and clinical obese subjects (Kanoski et al, 2011; Fukuda-Tsuru et al, 2014; Shah and Vella, 2014; Decara et al, 2016; Rondanelli et al, 2016; Xu et al, 2016). It is important to note, the tissue-specific modulation of lipid metabolism and WAT remodeling of GLP-1 represents a molecular mechanism in mediating GLP-1's anti-obesity actions (Decara et al, 2016; Xu et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…In our current study, the mice were subjected to the CLAMS system for analysis of metabolic status at the end of the experiment, but the weight reduction effect was seen after the first drug injection and maintained throughout the experiment, rendering the possibility that we might have missed the best time window to quantify EE that significantly influences body weight gain. Nevertheless, our data that Supaglultide-treated mice demonstrated a concomitantly increased trend of EE both on per-whole-animal and BW-normalized basis suggested that supaglutide exerted a regulatory effect on the energy expenditure of the obese mice, which is in good agreement with previous studies in both preclinical and clinical obese subjects (Kanoski et al, 2011; Fukuda-Tsuru et al, 2014; Shah and Vella, 2014; Decara et al, 2016; Rondanelli et al, 2016; Xu et al, 2016). It is important to note, the tissue-specific modulation of lipid metabolism and WAT remodeling of GLP-1 represents a molecular mechanism in mediating GLP-1's anti-obesity actions (Decara et al, 2016; Xu et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Possible mechanisms involved in the reduction of hepatic fat accumulation after GLP-1RAs intervention include an enhancement of hepatic lipophagy, a reduction in lipid synthesis, VLDL overproduction and lipotoxicity, and a change in hepatocyte enzyme expression levels, which favors a switch in energy utilization from carbohydrate to lipid (Panjwani et al 2013, Taher et al 2014. Induction of autophagy via the AMPK/mTOR pathway (Decara et al 2016) was also reported as one of the possible mechanisms. Other studies demonstrated…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the effect occurring centrally, GLP‐1 increased cAMP and AMPK phosphorylation in hepatocytes, resulting in the downregulation of lipogenic enzymes and upregulation of lipolytic CPT1 . Recent studies in high‐fat‐fed rodents treated with GLP‐1 analogs indicated that the specific reduction in liver steatosis and very low‐density lipoprotein (VLDL) overproduction was associated with decreased expression of main elements involved in lipogenesis (phospho‐ACC), peroxisomal β‐oxidation (ACOX1) and lipid flux (PPARγ) in the liver, as well as increased expression of lipolytic genes ( Hsl , Vlcad , Acox1 ) in adipose tissue . Interestingly, a recent study indicated that UCP1, a major regulator of non‐shivering thermogenesis, was specifically downregulated in the muscle of obese rats treated with liraglutide and suggests a link between uncoupling proteins and the expression of peroxisome proliferator‐activated receptors .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in high‐fat‐fed rodents treated with GLP‐1 analogs indicated that the specific reduction in liver steatosis and very low‐density lipoprotein (VLDL) overproduction was associated with decreased expression of main elements involved in lipogenesis (phospho‐ACC), peroxisomal β‐oxidation (ACOX1) and lipid flux (PPARγ) in the liver, as well as increased expression of lipolytic genes ( Hsl , Vlcad , Acox1 ) in adipose tissue . Interestingly, a recent study indicated that UCP1, a major regulator of non‐shivering thermogenesis, was specifically downregulated in the muscle of obese rats treated with liraglutide and suggests a link between uncoupling proteins and the expression of peroxisome proliferator‐activated receptors . Fatty acid flux and utilization to activate energy expenditure were particularly striking in non‐obese, non‐diabetic rats because of an increased expression of elements involved in lipogenesis (ACC, FAS, SCD1), fatty acid β‐oxidation (PPARα/γ, CPT1b) and thermogenesis (UCP1) in WAT and muscle .…”
Section: Introductionmentioning
confidence: 99%